Jomlo sampai Halal: Refleksi Sosiologis Budaya Generasi Milenial pada Mahasiswa Jomlo di IAIN Pontianak - Khairunnisyah, Khairunnisyah; Prasojo, Zaenuddin Hudi (JSW (Jurnal Sosiologi Walisongo), 2019)
The article is based on the fact that â€œjomloâ€ or being single has become a new trend as a sociological phenoÂmenon and the product of the practice of hijrah within the life of Muslim youth, especially Indonesian Muslim students. The concept of dating for those who practice the "men-jomlo" is very important in this work today. They, in fact, have unintentionally started to create a new culture of being njomlo although they are not being involved in a community designed for those practicing njomlo. This work attempts to provide analytical discussions on the concept of dating according to the students who practice the njomlo, what they mean by jomlo to halal, and their motivation to practice the njomlo. With the support of qualitative data, the work provides important findings on the practice of njomlo by the students of IAIN Pontianak. First, generally, the students agree that dating tends to lead to negative than positive attitudes so that they decide to choose being single or njomlo until they get married for halal relationship. Second, they believe that Islam does not have a concept of dating as understood by the youth today in the modern world and there is no Islamic dating. Third, religious conciseness has become the main element to motivate them so that they tend to rather choose to practice njomlo until they find their halal wife as they say â€œjomlo sampai halal."